1989
DOI: 10.1111/j.1151-2916.1989.tb07652.x
|View full text |Cite
|
Sign up to set email alerts
|

Metastability of the Martensitic Transformation in a 12 mol% Ceria‐Zirconia Alloy: II, Grinding Studies

Abstract: Observations of the grinding-induced transformation in singlephase Ce-TZP materials, referred to in an earlier paper, are presented. Two techniques were used to grind the surface: by hand in a slurry of abrasive particles and with a high-speed diamond-impregnated wheel. Significant differences in X-ray diffraction profiles between the two grinding methods was observed. Limited monoclinic Zr02 was detected on the machineground surface, along with the reversal of the tetragonal ZrOz (200) peak intensities. On th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
48
0
1

Year Published

1995
1995
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(56 citation statements)
references
References 10 publications
7
48
0
1
Order By: Relevance
“…The lower flexural strength values, compared to those reported by the manufacturers of Y-TZP, may be due the fact that specimens were only sintered, rather than sintered and polished as recommended by the ANSI/ADA specification for dental ceramics (23). Furthermore, Swain and Hannink (18) reported that hand ground Ce-TZP surface contained almost five times more monoclinic zirconia than severely machine ground surface of the same material.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The lower flexural strength values, compared to those reported by the manufacturers of Y-TZP, may be due the fact that specimens were only sintered, rather than sintered and polished as recommended by the ANSI/ADA specification for dental ceramics (23). Furthermore, Swain and Hannink (18) reported that hand ground Ce-TZP surface contained almost five times more monoclinic zirconia than severely machine ground surface of the same material.…”
Section: Discussionmentioning
confidence: 99%
“…Wet hand-grinding with a fine-grit diamond rotary cutting instrument is another surface modification described in the literature, with a favourable effect on the strength of zirconia (11,17). Previous investigators advocated fine grinding as an alternative method for roughening zirconia reconstructions in the absence of air-abrasion armamentarium (10,12,18).…”
Section: Introductionmentioning
confidence: 99%
“…The addition of three molecules of Y 2 O 3 results in a stabilising tetragonal phase at room temperature, which, as a result of a transition to a monoclinic phase can prevent the pro gression of cracks in the ceramic (Trans formation strengthening). [24][25][26][27] Examples of Zirconium oxide blocks: Lava Frame (3M ESPE), Cercon Smart Ceramics (DeguDent), Everest ZS und ZH (KaVo), inCoris Zr (Sirona), In-Ceram YZ (Vita), zerion (etkon) and Zeno Zr (Wieland-Imes)…”
Section: Yttrium Stabilised Zirconium Oxide (Zro 2 Y-tzp)mentioning
confidence: 99%
“…It was shown that grinding and sandblasting promote a severe damage on dental prosthesis mainly during excess glass removal. Despite the use of a water coolant, Swain and Hannink [17] dealing with zirconia, observed that an excessive heat generated during grinding could promote changes in its microstructure. In this case, this heating could promote crack healing which did not occurred during sandblasting.…”
Section: Resultsmentioning
confidence: 99%